Factors Influencing Liquidity Risk of Islamic Banks in Indonesia : A Systematic Literature Review - Pranoto Effendi (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Liquidity issues have become crucial in the banking sector during the global economic recovery following the COVID-19 pandemic, presenting significant challenges that Islamic banks must proactively address. This article systematically examines the factors influencing liquidity risk in Islamic banks in Indonesia using the systemic literature review (SLR) methodology following the PRISMA procedure. A comprehensive search of the Google Scholar Database was conducted using three key keywords: "liquidity risk," "Islamic banks," and "Indonesia." After a rigorous screening and selection process, fifteen relevant articles were identified for in-depth analysis. The findings reveal that the key determinants of liquidity risk can be categorized into three groups: internal factors, intermediary factors, and external macroeconomic factors. A clear implication of these findings is that Islamic banks need to manage their liquidity risk more effectively by adopting a holistic strategy that simultaneously and more seriously addresses all three categories of factors. This integrative approach is crucial for managing the complexity of the post-pandemic financial landscape.